Bloomsbury professional vat 2020/21 - Needham, Andrew (London [England] : Bloomsbury Professional, 2020)
"This annual guide to VAT provides clear and simple coverage enabling the reader to grasp current VAT law confidently. With a wealth of practical examples, this book is an ideal guide for tax advisers dealing with VAT, and small business proprietors. Value Added Tax 2020/21 has been updated to include the following: - The VAT changes resulting from the pandemic including: - The bringing forward of the zero-rating of electronic publications - The introduction of a temporary zero-rate for PPE - The temporary 5% reduced rate for the hospitality industry - Brexit changes - The introduction of postponed accounting - Zero-rating of women's sanitary products This accessible reference guide has a user-friendly structure with 'signposts' at the beginning of each chapter to summarise key topics and 'focus points' throughout to highlight important issues, as well as numerous worked examples demonstrating how to apply the main principles in practice. Andrew Needham is a Chartered Tax Adviser and heads VAT Specialists Ltd. Andrew has a degree in Law from UCNW Bangor and is a specialist in indirect taxes, international tax and land and property issues. He is also a lecturer on VAT issues. Andrew has over 30 years' experience in VAT having spent 7 years in HM Customs & Excise, firstly as a VAT inspector, then as a departmental trainer, and finally in a headquarters policy unit dealing with the introduction of the EU single market."--
Chapter 1 How VAT works-an outline of the system -- Chapter 2 Where to find the law -- Chapter 3 When to register and deregister for VAT -- Chapter 4 VAT groups -- Chapter 5 The VAT return -- Chapter 6 So what must VAT be charged on? -- Chapter 7 Time of supply-when VAT must be paid -- Chapter 8 The value of supply rules -- Chapter 9 So what is reduced-rated? -- Chapter 10 So what is zero-rated? -- Chapter 11 So what is exempt? -- Chapter 12 Is there one supply or two? -- Chapter 13 What can a business recover input tax on? -- Chapter 14 What is a valid tax invoice? -- Chapter 15 Credit notes -- Chapter 16 Bad debt relief -- Chapter 17 What records are required? -- Chapter 18 VAT housekeeping for finance directors -- Chapter 19 How does a business keep up to date on changes in VAT? -- Chapter 20 Exports and removals of goods -- Chapter 21 Imports and acquisitions of goods -- Chapter 22 EC Sales Lists and Intrastat returns -- Chapter 23 Exports and imports of services -- Chapter 24 Partial exemption -- Chapter 25 The Capital Goods Scheme -- Chapter 26 Property -- Chapter 27 Recovery of foreign VAT: the 8th and 13th Directives -- Chapter 28 What is a business? -- Chapter 29 Agency is special -- Chapter 30 Joint ventures -- Chapter 31 The Second-hand Goods Scheme -- Chapter 32 The Retail Schemes -- Chapter 33 Annual Accounting Scheme -- Chapter 34 Cash Accounting Scheme -- Chapter 35 The Flat Rate Scheme for Small Businesses -- Chapter 36 The Flat Rate Farmers' Scheme -- Chapter 37 The Tour Operators' Margin Scheme -- Chapter 38 Buying or selling a business -- Chapter 39 Assessment and VAT penalties -- Chapter 40 Taking an appeal to the Tribunal
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Value-added tax -- Law and legislation -- Great Britain; Electronic books